PELATIHAN PENYUSUNAN LAPORAN KEUANGAN DENGAN SISTEM AKUNTANSI YANG AKURAT DAN TRANSPARAN PADA POKDARWIS (KELOMPOK SADAR WISATA) DI DESA WISATA TALUAK BUO - Sari, Yosi Puspita; Muhammad Pondrinal (Jurnal Abdi Insani, 2025)
This community service program was carried out to improve the financial management capacity of the Tourism Awareness Group (Pokdarwis) in Taluak Buo Tourism Village. Prior to the training, an initial survey showed that only about 30% of Pokdarwis members understood basic accounting principles, and only 25% were able to prepare simple financial reports. In addition, the existing financial recording system did not meet accurate and transparent standards, making it difficult to evaluate performance and provide accountability for funds. Through a participatory training program, participants received materials on basic accounting principles, transaction recording techniques, and the preparation of financial statements in accordance with established standards. The activities were conducted through interactive lectures, hands-on practice sessions, and intensive mentoring. Post-training evaluations showed a significant improvement, with 85% of participants understanding basic accounting concepts and 80% being able to prepare financial statements in a standardized and transparent format. Moreover, the Pokdarwis succeeded in producing financial reports for the current period that were more organized, complete, and accountable to all stakeholders. This program is expected to promote better financial governance, increase public trust, and support the sustainable management of Taluak Buo Tourism Village in the future.